(untitled) (Tempo e Argumento, 2021)
In August 1942, Brazil declared war on Germany and Italy. In the period following that declaration, there was intense mobilization of the Brazilian State to organize the foreign front - with the creation of the Brazilian Expeditionary Force - and the domestic one - with large-scale mobilization of civilian resources for the war effort. Historiographical production on the period has prioritized the analysis of the state’s action in this process, either through its participation in the conflict or through its authoritarian character and repressive mechanisms of mobilization and control of society. The studies on the actions of the entities of society, which, with some autonomy and diverse interests, also took part in the war effort, are somewhat rare. This work intends to analyze the mobilization of the major carioca football clubs during the World War II from a perspective of the relationships between the state and society during Estado Novo. The sources for the work are reportage published by the press in Rio de Janeiro and documents available in the clubs’ archives. It’s assumed that there was, albeit sparingly, some autonomous action of sectors of the carioca society for the war effort